2006
DOI: 10.1016/j.chembiol.2006.08.008
|View full text |Cite
|
Sign up to set email alerts
|

An Enzyme that Regulates Ether Lipid Signaling Pathways in Cancer Annotated by Multidimensional Profiling

Abstract: Hundreds, if not thousands, of uncharacterized enzymes currently populate the human proteome. Assembly of these proteins into the metabolic and signaling pathways that govern cell physiology and pathology constitutes a grand experimental challenge. Here, we address this problem by using a multidimensional profiling strategy that combines activity-based proteomics and metabolomics. This approach determined that KIAA1363, an uncharacterized enzyme highly elevated in aggressive cancer cells, serves as a central n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
210
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 173 publications
(223 citation statements)
references
References 52 publications
9
210
0
1
Order By: Relevance
“…For example, we have reported that monacylglycerol lipase is up-regulated across aggressive cancer cells and primary tumors where it controls release of FFAs from monoacylglycerols to fuel generation of FFA-derived oncogenic signaling lipids, such as LPA and PGE2 to drive malignant features of cancer (18). Chiang et al demonstrated that blocking of KIAA1363, a deacetylase of 2-acetyl MAGe, lowers levels of its neutral ether lipid product MAGe, which decreases the levels of its downstream metabolite LPAe, leading to impaired cellular migration and tumor growth (15). It will be of future interest to determine the effects of polypharmacologically blocking several of these pathways simultaneously in cancer cells to achieve maximal anticancer activity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, we have reported that monacylglycerol lipase is up-regulated across aggressive cancer cells and primary tumors where it controls release of FFAs from monoacylglycerols to fuel generation of FFA-derived oncogenic signaling lipids, such as LPA and PGE2 to drive malignant features of cancer (18). Chiang et al demonstrated that blocking of KIAA1363, a deacetylase of 2-acetyl MAGe, lowers levels of its neutral ether lipid product MAGe, which decreases the levels of its downstream metabolite LPAe, leading to impaired cellular migration and tumor growth (15). It will be of future interest to determine the effects of polypharmacologically blocking several of these pathways simultaneously in cancer cells to achieve maximal anticancer activity.…”
Section: Resultsmentioning
confidence: 99%
“…The physiological roles of ether lipids are not well understood, but they have been implicated in maintaining physicochemical properties of cell membranes, such as membrane fluidity, membrane fusion events, and lipid raft microdomains (9,10). Certain ether lipids, such as lysophosphatidic acid-ether (LPAe) or platelet-activating factor-ether (PAFe), are signaling molecules that have been shown to possess bioactive and even oncogenic properties through binding specific receptors (11)(12)(13)(14)(15). In the late 1960s, Snyder and Wood first reported that rodent and human tumors possess significantly higher levels of ether lipids relative to normal tissue.…”
mentioning
confidence: 99%
“…Since cathepsin B is suspected of facilitating tumor invasion, this compound could potentially be used as a lead target for cancer therapy. ABP-based assays using the serine hydrolase probe FP-rhodamine have also been applied to the discovery of novel, selective inhibitors of KIAA1363, a poorly characterized enzyme with highly elevated activity in invasive cancer cells [34,35]. This screen yielded valuable lead compounds that facilitated further study of the function of KIAA1363 in the metabolism of lipids.…”
Section: Enzyme Inhibitor Discovery and Verificationmentioning
confidence: 99%
“…Recent studies have demonstrated that serine hydrolase ABPP permits the classification of human cancer lines into functional subtypes on the basis of tissue of origin and state of invasiveness (3). Moreover, this approach has identified tumor-associated activities with roles in cell invasion, migration, and intravasation (1,3,4).…”
mentioning
confidence: 99%
“…functional proteomics | activity profiling | pancreatic cancer TGF-β signaling S erine hydrolases are central effectors of the proliferative, invasive, and migratory properties of tumors, with roles in growth factor activation, extracellular matrix degradation, and angiogenesis (1)(2)(3)(4). Serine hydrolase transcript and protein levels are elevated in many cancer cell lines and primary tumors, but the functional relevance of these changes remains unknown (3,5).…”
mentioning
confidence: 99%